Racial, ethnic, and socioeconomic disparities in pituitary surgery outcomes. (4th February 2016) - Goljo, Erden; Parasher, Arjun K.; Iloreta, Alfred M.; Shrivastava, Raj; Govindaraj, Satish
Abstract : Objectives/Hypothesis: To investigate the association of race, ethnicity, socioeconomic status, and hospital volume with outcomes in pituitary surgery. Study Design: Retrospective cross‐sectional study of the 2008‐2012 National (Nationwide) Inpatient Sample. Methods: Patient demographics, hospital characteristics, postoperative complications, and in‐hospital mortality for patients undergoing pituitary surgery were compared between white, black, and Hispanic patients. Hierarchal logistic regression analysis was used to assess the association of patient and hospital variables on complication rates. Results: A total of 8, 812 patients met the inclusion criteria, and 5, 924 (67.2%) patients were white, 1, 590 (18.0%) were black, and 1, 296 (14.7%) were Hispanic. Black and Hispanic patients were more likely to live in the poorest income areas, be insured with Medicaid, and be treated at lower‐volume pituitary surgery centers. Patients with Medicaid had a higher likelihood of complications compared to Medicare patients, whereas patients with private insurance were significantly less likely to experience any complications. Likelihood of complications was significantly higher for patients treated at lower‐volume pituitary surgery centers. When controlled for patient and hospital characteristics, regression analysis showed that the likelihood of postoperative complications was higher in black and Hispanic patients compared to white patients. Conclusions: Racial, ethnic, and socioeconomic disparities exist for outcomes after pituitary surgery. Black and Hispanic patients have worse postoperative outcomes compared to white patients, as well as disproportionate utilization of Medicaid and low‐volume pituitary surgery centers. Further investigations are necessary to uncover the sources of these disparities in an effort to provide safer and more affordable care to all patients. Level of Evidence: 2c. Laryngoscope, 126:808–814, 2016